NUSYUZ DAN SYIQAQ SERTA FUNGSI HAKAMAIN DALAM KASUS SYIQAQ - Abdul Hafidz Miftahuddin; Amilatun Nafiah (ADIDAS: Asosiasi Dosen Syari'ah STAI Darussalam Nganjuk, 2023)
The rift in the household comes from the failure of the rules set by Allah in the life of husband and wife according to their rights and obligations. Thus Allah anticipates the possibility of divorce and places divorce as the last alternative that cannot be avoided. Things that can occur as a sign of a family breakdown include nusyuz and syiqaq. Including nusyuz acts, namely the wife is reluctant, even refusing to comply with her husband's invitation, even though she is busy doing something. Syiqaq arises when the husband or wife or both do not carry out the obligations that must be borne by them. If the husband and wife are unable to resolve the conflict, then it becomes the obligation of the Muslim congregation to prioritize the obligations of the families of both parties to reconcile it through the presence of hakamain.